Simultaneous field measurements of terpene and isoprene emissions from two dominant Mediterranean oak species in relation to a north American species - Kesselmeier, J; Bode, K; Schafer, L (Atmospheric Environment, 1998)
ÐWe investigated the emission of monoterpenes and isoprene from tree species growing at a site near Montpellier (South France). We compared the emission pattern and behaviour of two important oak species representative of the Mediterranean ecosystem, namely, Quercus ilex (Holm oak), a strong monoter- pene emitter, and Quercus pubescens (White oak), a strong isoprene emitter by measuring the two species growing side by side simultaneously. Additionally, we included a Californian oak species Quercus agrifolia (Coast Live Oak), which is anatomically and morphologically comparable with Quercus ilex. The data show that Live Oak and Holm oak though they appear identical, di¤er as far as the emission of terpenoids is concerned, emitting isoprene or terpenes, respectively. The isoprene emitting White oak and the monoter- pene emitting Holm oak react identically to the same environmental conditions, ßuctuating light and temperature, indicating that close metabolic pathways are involved in the actual emission of the C5 and C10 compounds from these two species, as seen under Þeld conditions. ( 1998 Elsevier Science Ltd. All rights reserved
Keywords: isoprene; Monoterpenes; oak; quercus agrifolia; Quercus ilex; Quercus pubescens; volatile biogenic hydrocarbons